Large herbivore grazing and non-native plant invasions in montane grasslands of central Argentina - Loydi, Alejandro (2010)
Grazing by large herbivores has the potential to facilitate invasion of natural grasslands by non-native plant species. It is expected that both herbivore identity and plant community type modulate the effect. The objective of this study was to evaluate the impact of grazing on non-native plant species richness and cover in a montane grassland of central Argentina, as related to herbivore identity (horse or cattle) and plant community type. The study was conducted in piedmont valleys of the Ventania Mountains. The area is occupied by two major types of plant communities: short-needlegrass and tall-tussock grasslands. The former occupies poor soils and has higher plant species diversity compared to the latter which grows on rich soils. Part of the study area is devoted to cattle husbandry, part is inhabited by feral horses, and part has been free of grazing by large herbivores for the last 15 years. We compared non-native richness and percentage cover at three different grazing situations (horse grazing, cattle grazing, grazing exclusion) and at two levels of plant community type (short-needlegrass grassland and tall-tussock grassland) at the end of the growing season in 2006 and 2007. Thirty-one non-native plant species were found growing in the study area. Grazing increased non-native species richness and cover. Invasibility was highest under horse grazing and on communities in resource-rich soils. Our results are consistent with the hypothesis that grazing by large non-native herbivores can facilitate non-native plant species invasion into natural grasslands. They also suggest that herbivore identity and community type modulate the effect of large herbivore grazing on grassland invasion by non-native plant species.